Dinamika UMKM Terdampak Pandemi: Problem-Based Learning Mahasiswa - Kuncorojati, Marcelinus Anggun Dananto; Purnamasari, Vena; Hastuti, Rini (Patria : Jurnal Pengabdian Kepada Masyarakat, 2024)
Tangan Terampil Indonesia is a social organization dedicated to empowering communities through entrepreneurship development, embodying the tagline “We Develop People Through Entrepreneurship.” The organization collaborates with various stakeholders, including government agencies, state-owned enterprises, the private sector, and universities, to foster an entrepreneurial ecosystem that makes a direct impact. One notable partnership is with the Accounting Study Program at FEB Soegijapranata Catholic University. This collaboration focuses on mentoring micro, small, and medium enterprises (MSMEs) to enhance their financial literacy. During the COVID-19 pandemic, many MSMEs faced significant challenges, raising concerns about their business continuity. A considerable number of these enterprises lacked adequate financial records. To address this, a service team provided assistance in creating financial records, which were then analysed by students to evaluate the feasibility of these businesses. The outcomes included improved financial management capabilities for the MSMEs and invaluable consulting experience for the students, who presented their analysis to the clients.